Culture is Digital and the shifting terrain of UK cultural policy. Issue 7 (10th November 2022) - Wright, David; Gray, Clive
ABSTRACT: In this paper, a change to the remit and title of a UK government department provides a starting point for reflection on the growing role of digital technologies in the re-imagination of UK cultural policy. An early strategic report produced by the re-named DCMS was entitled Culture is Digital . Identifying the UK's cultural and technology sectors as 'the ultimate power couple, ' this report directs the cultural sector towards the use of technology to enhance public engagement and to improve technical skills through the development of collaborations with technology companies. Reflecting on the place of DCMS in UK cultural policymaking and drawing on analysis of this report and associated strategic documents, including responses and updates produced in the light of the Covid pandemic, the paper analyses the claims made about the elision between culture and the digital and their consequences for the status of cultural policy within the British state.